Pengelolaan Aset SMKN di Provinsi Banten Pasca Peralihan Kewenangan Dari Kabupaten Ke Provinsi - Ujang Suryana (NIAGARA Scientific Journal, 2022)
This study discusses SMKN Asset Management in Banten Province After the Transfer of Authority from District to Province. The aim of the research is to determine SMKN Asset Management in Banten Province after the Transfer of Authority from District to Province. This study uses a descriptive qualitative approach. Determination of informants using purposive sampling technique. Data collection techniques through observation, direct interviews and documentation. Testing the validity of the data uses triangulation of data sources and member checks associated with Siregar's regional asset management theory (2004). Data analysis techniques using Miles and Hubberman. The results of the study show that SMKN Asset Management in Banten Province After the Transfer of Authority from District to Province is still not going well.regarding documents of ownership and certificates that are not properly inventoried because all legal audits require supporting resources for the sustainability of assets to continue to run well, Every report in the Office of Education, SMKN 1 Cikande and SMKN Agriculture must run well without having to rely on asset managers who bear the responsibility of each Regional Apparatus Organization.Potential assets must be used properly and utilized as best as possible and must be managed and cared for according to their respective functions.